Characteristics of the Oldest Slavic Pottery. The Example of a Pot from Structure SO 11 from the Murska Sobota - Nova Tabla Site (Archaeologia Adriatica, 2009)
In the period from 1999 to 2008, as part of motorway construction works, comprehensive archaeological excavations were conducted in the part of the Prekmurje region between the banks of the Mura River and the town of Murska Sobota. Numerous remains were unearthed that can be associated with the first Slavic settlement in the area of the Eastern Alps and Northern Adriatic. In Nova Tabla, 189 residential structures from the early Middle Ages were examined. The settlement also contained a group of 11 skeleton graves, unearthed on the south-western margin of Roman tumuli with incineration graves. On the basis of typology and comparison with other related sites, and with the help of numerous radiocarbon dating tests, the Nova Tabla settlement has been divided into two larger cultural and time horizons: Murska Sobota 1 and 2, with interstages of development encompassing the period from the 6th until the beginning of the 9th century. The inventory of pit SO 11 with a fragment of a simply made small jug with a loosely curved mouth can be classified as belonging to the oldest early Slavic settlement remains in Nova Tabla. The reconstructed small pot (Fig. 3) with its slender shaped body, indefinitely shaped mouth, hand-made with a porous undecorated surface, is a good representative of Prague Culture pottery (cf. M. KUNA et al., 2005, 347) and has the recognisable workmanship characteristic of the earthenware of the first Slavic horizon of Murska Sobota 1. Apart from the light non-oxidised burning, the uneven, porous surface of the entire vessel is also typical of this facture. In the Slovenian archaeological context, a porous surface on ceramic vessels and carved, wave-shaped decorative lines are typical of early mediaeval Slavic pottery. Generally, the porosity of the surface is associated with admixtures of plant origin, usually with grains of wheat, which usually get completely burned in the process of baking (G. FUSEK, 1994, 16; M. KUNA et al., 2005, 339). One of the possible ways of achieving a porous surface was adding crushed coal. This method is hard to prove but was successfully carried out as part of an experiment in making Slavic pottery (M. GUŠTIN, 2005, 37; I. BAHOR, 2010). The newcomers’ distinctive pottery with its porous surface remained the only type of pottery over a short period of time. Soon after its appearance, in the first half of the seventh century, the first shaping and technological developments in early Slavic pottery from Nova Tabla and other sites had started.
Keywords: early Slavic pottery; Nova Tabla near Murska Sobota; the Slavs